The Method of Signal Decomposition to Reduce the PAPR - Yinghua Tong; Shengling Geng (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
A new method of signal decomposition based on the baseband to reduce the PAPR which Decompose the OFDM signal into two signals, The new method  and its degree of PAPR improvement are introduced in detail . Two thresholds are introduced, compare threshold Tc and decompose threshold Td .Simulation the results in different thresholds .The results show that the method can reduce the PAPR greatly. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3389